Mitochondrial biogenesis as a result of exercise - Neufer, Darrell (Henry Stewart Talks, 2007)
Introduction to skeletal muscle fiber types, Mitochondrial morphology in muscle fiber types, Mitochondrial adaptations to exercise training, Mitochondrial content, physical activity & aging, Signaling to mitochondrial biogenesis, Endurance performance & mitochondria content
Archived at 2018/05/31